Особенности речевой деятельности учителей-логопедов - Фомина, Наталья; Леева, Анна (Lesya Ukrainka Eastern European National University, 2015)
Аннотация. В статье рассматривается проблема исследования проявления особенностей личности в речевой деятельности. Подчеркивается, что речь как высшая психическая функция определяет все развитие человека и является одним из инструментов осуществления педагогической деятельности учителей-логопедов, работающих с лицами с речевыми нарушениями. Поскольку их речь должна выступать в качестве образца, к ней предъявляются очень высокие требования: она должна быть точной, правильной, связной, логичной, убедительной и выразительной. Раскрываются возможности речевой диагностики различных особенностей языковой личности, т.е. личности, выраженной через язык в речи. В рамках концепции Н. А. Фоминой по комплексному исследованию проявлений личности и ее свойств в речи анализируются языковые, речевые, содержательно-смысловые особенности текстов-высказываний учителей-логопедов на актуальную и личностно значимую для них тему «Учитель», а также отражение в текстах их мотивационно-целевых, когнитивных, эмоциональных, регулятивных характеристик. Abstract. The article deals with the problem of studying the demonstrations of personality characteristics in speech activity. The paper emphasizes that speech is the highest mental function which determines all human development and one of the tools of pedagogical activity teacher-logopedists working with people with speech disorders. As their speech has to act as an example, very great demands are made of it: it has to be exact, correct, coherent, logical, convincing and expressive. The study highlights that speech can serve as a means of modern diagnostic features of the person, as in speech activity they are reflected. Study of features manifestation of personality in speech activity teacher-logopedists conducted within the concept of N. A. Fomina, which allows to consider the properties of the individual as a system, features the language of the person in the unity of its linguistic and psychological characteristics, which are reflected in the text – the product of speech activity. To do this, teacher-logopedists were asked to write text about the personal importance of the theme of “Teacher”.
Keywords: личность; речевая деятельность; текст; учитель-логопед; лингвальные (языковые, содержательно-смысловые) характеристики речи; психологические (мотивационные, когнитивные, эмоциональные, регулятивные) особенности личности; personality, speech activity, text, teacher-logopedist, linguistic (lingual, notional) characteristics of speech and psychological (motivational, cognitive, emotional, regulative) characteristics of personality